Is Africa Turning Against the West? - Carbone, Giovanni; Ragazzi, Lucia (ISPI Publications, 2023)
In the past few years, the evolving global landscape has drawn increasing attention to the positioning of African countries on major international issues. Much emphasis has been placed on African voting and diplomatic stances in international fora, political rhetoric and protests, all seemingly pointing to a shift towards a more critical approach vis à vis traditional Western partners. At the same time, non-alignment, a notion that for some retained a merely historical value, has gained new impetus as a principle guiding a number of countries of the Global South, suggesting a break in the relationship with old and new partners. This report investigates the nature and reasons of the growing anti-Western sentiment in sub Saharan Africa, combining an analysis of the current international context with a look at the long term. Is the gap between Africa and the West really expanding? What are the reasons and the possible consequences? What can be done to turn criticism into a more profound, mutual understanding?